A comparative study on the modulatory role of mesoporous silica nanoparticles MCM 41 and MCM 48 on growth and metabolism of dicot Vigna radiata - Mitra, Sutanuka (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.